Gambaran Career Happiness Plan Pada Dosen - Anggun Resdasari Prasetyo (Jurnal Psikologi Undip, 2015)
Happiness at work is one of important aspects need to be developed by individuals from any kind of profession. One of those profession is lecturer. Lecturer with happiness at work tends to be more productive and produce new and innovative ideas. This study aims to understand career happiness plan profile among lecturers. A descriptive study was conducted on 13 lecturers. Developmental goals measurment called Career Happiness Plan was used in this study to give information about factors contributed to lecturers’ happiness as well as information about how lecturers cope with stress, crisis, and change or challenge situation at workplace. The result showed that factors affected happiness on lecturers were relationship to others, full engagement, meaning finding (spirituality), and career development.